Lack of Evidence for a Direct Interaction of Progranulin and Tumor Necrosis Factor Receptor-1 and Tumor Necrosis Factor Receptor-2 From Cellular Binding Studies - Lang, Isabell; Füllsack, Simone; Wajant, Harald (Frontiers in Immunology, 2018)
Progranulin is a secreted anti-inflammatory protein which can be processed by neutrophil proteases to various granulins. It has been reported that at least a significant portion of the anti-inflammatory effects of progranulin is due to direct high affinity binding to TNFR1 and TNFR2 and inhibition of TNF-induced TNFR1/2 signaling. Two studies failed to reproduce the interaction of TNFR1 and TNFR2 with progranulin but follow up reports speculated that this was due to varying experimental circumstances and/or the use of progranulin from different sources. However, even under consideration of these speculations, there is still a striking discrepancy in the literature between the concentrations of progranulin needed to inhibit TNF signaling and the concentrations required to block TNF binding to TNFR1 and TNFR2. While signaling events induced by 0.2 – 2 nM of TNF have been efficiently inhibited by low, near to equimolar concentrations (0.5 – 2.5 nM) of progranulin in various studies, the reported inhibitory effects of progranulin on TNF-binding to TNFR1/2 required a huge excess of progranulin (100-1000 fold). Therefore, we investigated the effect of progranulin on TNF binding to TNFR1 and TNFR2 in highly sensitive cellular binding studies. Unlabeled TNF inhibited > 95 % of the specific binding of a Gaussia princeps luciferase (GpL) fusion protein of TNF to TNFR1 and TNFR2 and blocked binding of soluble GpL fusion proteins of TNFR1 and TNFR2 to membrane TNF expressing cells to > 95 %, too. Purified progranulin, however, showed in both assays no effect on TNF-TNFR1/2 interaction even when applied in huge excess. To rule out that tags and purification- or storage-related effects compromise the potential ability of progranulin to bind TNF receptors, we directly co-expressed progranulin, and as control TNF, in TNFR1- and TNFR2-expressing cells and looked for binding of GpL-TNF. While expression of TNF strongly inhibited binding of GpL-TNF to TNFR1/2, co-expression of progranulin had not effect on the ability of the TNFR1/2-expressing cells to bind TNF.